Effect of harvest rate, waste loading, and stocking density on the yield of duckweeds - M. Said, M. Zaki; Culley, Dudley D.; Standifer, Leon C.; Epps, Ernest A.; Myers, Robert W.; Boney, Steve A. (Wiley, 1979)
In an outdoor tank culture system with 10 to 20 g/liter fresh dairy cattle manure dilutions (ca 60 to 120 mg/liter TKN), maximum growth of duckweed (Spirodela polyrhiza) was obtained when harvested at 6‐day intervals. An initial stocking of 70 g fresh duckweed/0.14 m2 (505 g/m2) gave the highest yield when the excess fresh biomass (34.4 g) was harvested daily or 33% of the standing stock. The extrapolated yield of dry duckweed harvested daily was 14.9 g/m2/day and was 58% higher than one weekly harvest. Removal of excess growth daily gave higher yields than removing half the standing crop at doubling periods exceeding 2 days. Nitrogen, phosphorus, and potassium content of duckweed increased as water nutrients increased. The maximum dry weight values were: nitrogen, 6.96%; phosphorus, 1.50%; and potassium, 3.50%. The highest dry duckweed crude protein value recorded was 43.5% and the mean was 38.2% when the plants were cultured on 10 g fresh manure/liter of solution. Higher protein values were correlated with lower standing crop. Comparisons between the tank culture system and lagoon studies using mixed species culture are discussed. Extrapolation of lagoon data showed an annual dry weight mean yield of 1.76 kg/m2 and a maximum yield of 2.2 kg/m2 when one half of the plants were harvested weekly. Annually, in comparison 4.4 kg/m2 of S. polyrhiza were estimated from daily harvests in the tank system with corrections made for seasonal effects. Nutrient content of the duckweeds were similar under the two systems. Under both systems aeration did not increase yields over non‐aerated tests.